Genome-Wide Enhancer Analysis Reveals the Role of AP-1 Transcription Factor in Head and Neck Squamous Cell Carcinoma - Wang, Chen-Yu; Yu, Guang-Tao; Gao, Chuan; Chen, Ji; Li, Qing-Lan; Zhang, Lu; Wu, Min; Sun, Zhi-Jun; Li, Lian-Yun (Frontiers in Molecular Biosciences, 2021)
Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancer in the world, but its epigenomic features has not been determined. Here, we studied the chromatin landscape of active enhancers of HNSCC head tumor tissues by performing H3K27ac and H3K4me1 ChIP-Seq with a Tgfbr1/Pten double conditional knockout HNSCC mouse model. We identified 1248 gain variant enhancer loci (VELs) and 2188 lost VELs, as well as 153 gain variant super enhancer loci (VSELs) and 234 lost VSELs. Potential involved transcription factors were predicted with motif analysis, and we identified AP-1 as one of the critical oncogenic transcription factors in HNSCC and many other types of cancer. Combining transcriptomic and epigenomic data, our analysis also showed that AP-1 and histone modification coordinately regulate target gene expression in HNSCC. In conclusion, our study provides important epigenomic information for enhancer studies in HNSCC and reveals new mechanism for AP-1 regulating HNSCC.